IMPLICATION OF GROUP COMPANY EXPANSION TO MONOPOLY PRCTICE AND UNFAIR BUSINESS COMPETITION (Study Case : Coal Mining Industry) - Hartana, Hartana (Jurnal Komunikasi Hukum, 2020)
In relation with the coal mining business growth in Indonesia for the past 10 years, than it must also supported with the fulfillment of the applicable Laws, than the purpose of this disertationare, first, to know and to find the Laws which specifically regulates the expansion buoying of Group Company especially in coal mining sector.Second, to know about the implementation of Group Company expansion in coal mining sector. Third, to know, analyze, and to find the implication of Group Company expansion in mining sector toward monopoly practice and unfair business competition. The results of this research are, First, that the Law No. 4 Year 2009 regarding Mineral and Coal Mining regulates about the buoying of group company, mentioning that the IUP and IUPK owners are banned from involving their sister company and/or their affiliation in mining service industry located in their mining area, except they have the Minister’s License. Meanwhile maximum area ownership of IUP in group company is not restricted. Second, the most common group expansion in coal mining industry are by establishing holding company, acquisition and joint venture. The principal motive of these actions are economy and psychology. Third, group company expansion in coal mining industry implicates on abuseof dominant position and market control. The consequence are the addition of several new companies and also directly implies the ownership of the subsidiary's shares by the parent company. Of the 5 (five) coal mining companies studied when doing corporate actions, so that into 1 (one) group companies, the amount of coal production does not reach 50%. It is not proven to be denied Article 17 of Law no. 5 of 1999.